Outcomes for jejunal interposition reconstruction compared with Roux-en-Y anastomosis: A meta-analysis - Fan, Kai-Xi (World J Gastroenterol, 2015)
AIM: To compare the clinical outcomes between jejunal interposition reconstruction and Roux-en-Y anastomosis after total gastrostomy in patients with gastric cancer. METHODS: A systematic literature search was conducted by two independent researchers on PubMed, EMBASE, the Cochrane Library, Google Scholar, and other English literature databases, as well as the Chinese Academic Journal, Chinese Biomedical Literature Database, and other Chinese literature databases using “Gastrostomy”, “Roux-en-Y”, and “Interposition” as keywords. Data extraction and verification were performed on the literature included in this study. RevMan 5.2 software was used for data processing. A fixed-effects model was applied in the absence of heterogeneity between studies. A random effects model was applied in the presence of heterogeneity between studies. RESULTS: Ten studies with a total of 762 gastric cancer patients who underwent total gastrostomy were included in this study. Among them, 357 received jejunal interposition reconstruction after total gastrostomy, and 405 received Roux-en-Y anastomosis. Compared with Roux-en-Y anastomosis, jejunal interposition reconstruction significantly decreased the incidence of dumping syndrome (OR = 0.18, 95%CI: 0.10-0.31; P < 0.001), increased the prognostic nutritional index [weighted mean difference (WMD) = 6.02, 95%CI: 1.82-10.22; P < 0.001], and improved the degree of postoperative weight loss [WMD = 2.47, 95%CI: -3.19-(-1.75); P < 0.001]. However, there is no statistically significant difference in operative time, hospital stay, or incidence of reflux esophagitis. CONCLUSION: Compared with Roux-en-Y anastomosis, patients who underwent jejunal interposition reconstruction after total gastrostomy had a lower risk of postoperative long-term complications and improved life quality.